Analysis of Open Space at Engineering Faculty of UMJ: Physically Possible and Legally Permitted - Yeptadian Sari (International Journal of Built Environment and Scientific Research, 2020)
FT UMJ has nine programs which include undergraduate programs in civil engineering, electrical engineering, chemical engineering, mechanical engineering, industrial engineering, architecture, informatics engineering, D3 OAB and masters of chemical engineering. All programs are located in one building in the center of Jakarta that has strict land regulations. The fixed nature of the land, but the increasing number of requests or needs, makes land one of the most promising areas of investment. To improve efficiency on land limitations, it is necessary to optimize land use. But the fact is, there are still many lands that have not been used optimally for the land owner due to unfavorable reasons. Likewise for open space that owned by UMJ which is not utilized properly. The expected outcome of this research is the best utilization of FT UMJ open space by taking into account the criteria physically possible, legally permitted, financially feasible, and having maximum productivity.